State-of-the-art approaches for evidence-based springshed management to increase resilience to climate change in Nepal - International Water Management Institute (CGIAR Research Program on Water, Land and Ecosystems, 2019)
• A thorough understanding of spring systems is essential to design evidence-based springshed interventions. The necessary information can be collected by conducting hydrometeorological monitoring, hydrogeological assessments and isotope analysis. • Springs are recharged by a combination of both surface water and groundwater sources that may extend beyond administrative and surface water boundaries. Identification of the nature and seasonality of springs provides a basis for prioritization of springs and design of interventions. • Considering a broader landscape approach, integrating the management of forests, agricultural fields, soils and water systems over larger areas, is recommended for longterm springshed management and to ensure adequate water supplies under conditions of climate change.